Evaluasi Rencana Peningkatan Manajemen Aset Daerah Melalui Aplikasi Handal dan Terintegrasi di Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Tangerang - Khalifatunnisa, Khalifatunnisa; Budiati, Ayuning; Arenawati, Arenawati (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
This research aims to analyze the evaluation of the Tangerang Regency government's strategic plan for improving regional asset management through reliable and integrated applications, in this case, the ATISISBADA application in 2024, and what efforts are being made to improve performance. The research method used in this research is descriptive research using a qualitative approach. Data collection techniques use primary data obtained through interviews and secondary data obtained through observation and documentation. Researchers used the Miles and Huberman model of qualitative data analysis, namely data reduction, data presentation, and conclusion. This research shows that the ATISISBADA application has significantly increased the effectiveness, efficiency, and transparency of regional asset management while identifying areas that need to be improved regarding staff training and technological infrastructure. Implementing applications such as ATISISBADA (Inventory Management Application and Regional Property Information System) has helped increase the accuracy of asset recording, speeding up the financial administration process and reducing the potential for irregularities in regional property management. Even though it has provided significant benefits, several challenges are still found, such as limitations in integrity with other systems, as well as the need for improvements to a more capable technological infrastructure.